The coordination of major events in C4 photosynthesis evolution in the genus Flaveria - Lyu, M-JA; Gowik, U; Kelly, S; Covshoff, S; Hibberd, JM; Sage, RF; Ludwig, M; Wong, GK-S; Westhoff, P; Zhu, X-G (Springer Nature, 2021)
C4 photosynthesis is a remarkable complex trait, elucidations of the evolutionary trajectory of C4 photosynthesis from its ancestral C3 pathway can help us better understand the generic principles of the evolution of complex traits and guide the engineering of C3 crops for higher yields. Here, we used the genus Flaveria that contains C3, C3–C4, C4-like and C4 species as a system to study the evolution of C4 photosynthesis. We first mapped transcript abundance, protein sequence and morphological features onto the phylogenetic tree of the genus Flaveria, and calculated the evolutionary correlation of different features; we then predicted the relative changes of ancestral nodes of those features to illustrate the major events during the evolution of C4 photosynthesis. We found that gene expression and protein sequence showed consistent modification patterns in the phylogenetic tree. High correlation coefficients ranging from 0.46 to 0.9 among gene expression, protein sequence and morphology were observed. The greatest modification of those different features consistently occurred at the transition between C3-C4 species and C4-like species. Our results show highly coordinated changes in gene expression, protein sequence and morphological features, which support evolutionary major events during the evolution of C4 metabolism.